A Simple Predictive Index of the Abdominal Shape for Postoperative Complications After Laparoscopy-Assisted Distal Gastrectomy for Gastric Cancer - Tao, Wei; Cheng, Yu-Xi; Liu, Xiao-Yu; Zhang, Bin; Yuan, Chao; Peng, Dong; Zhang, Wei (Frontiers in Surgery, 2021)
Background The purpose of this study was to explore the effect of abdominal shape on the short-term surgical outcomes. Methods This was a retrospective study that included 425 patients undergoing laparoscopic distal gastrectomy plus D2 lymph node dissection (LADG) from January 2013 to January 2021. The abdominal parameters, including the shortest distance of the pancreas from the anterior abdominal skin (PAAD), the lower sternum angle (LSA), the thickness of the subcutaneous fat at the navel level (SFT), the anteroposterior diameters (APD) and the left-right diameters (LRD) at the navel level, the distance from the xiphoid process to the navel (XND) and the distance from the xiphoid process to the pubis (XBD), were calculated by preoperative abdominal computed tomography (CT) imaging. The parameters and short-term surgical outcomes were analyzed. Results In males, the number of retrieved lymph nodes was significantly higher in patients with a lower APD group (p=0.031). The operation time was significantly shorter in the lower body mass index (BMI) (p=0.007), lower LSA (p=0.035), lower PAAD (p=0.000), lower SFT (p=0.004), lower APD (p=0.000) and lower LRD (p=0.014) groups. The estimated blood loss was significantly less in the lower BMI (p=0.035), lower LSA (p=0.001), lower PAAD (p=0.012), lower SFT (p=0.003), lower APD (p=0.000) and lower LRD (p=0.005) groups. The complications were fewer in the lower LSA (p=0.012), lower APD (p=0.043) and lower LRD (p=0.023) groups. In females, the postoperative hospital stay was shorter in the lower PAAD (p=0.027) and lower SFT (p=0.004) groups, and the lower SFT group had fewer complications (p=0.020). Furthermore, in multivariate analysis, higher PAAD (p=0.037, odds ratio=1.030, 95% CI=1.002-1.059) was an independent factor for predicting postoperative complications in males. Conclusion Various abdominal shapes can affect the difficulty of LADG. Higher PAAD is a simple independent index for predicting postoperative complications in males.